Bentuk Model Nonlinear untuk Portofolio Optimal dan Penyelesaiannya Menggunakan Metode Separable Programming - Uswati Hasnah; Suherman Suherman (UNIVERSITAS NEGERI PADANG, 2018)
Abstract – Investment is a business that is carried out in the form of placing funds in order to obtain profits in the future. When investing, an investor always expects maximum return with minimal risk. In other words, investors need to form an optimal portfolio. This is related to optimization theory. For this reason, an optimal nonlinear model portfolio will be formed, along with the solution, using the Separable Programming method. The steps taken are to form a nonlinear model for optimal portfolios, then apply the model to investment for stock in the Bank Rakyat Indonesia (BBRI) and Bank Central Asia (BBCA), then complete the model using Separable Programming. Based on the results of the study, the optimal portfolio nonlinear model is obtained, namely the total expected return minus the portfolio risk. Completion of the model using Separable Programming results in a comparison of the proportion of funds that will be invested in BBRI and BBCA stocks